Blockade of Fgfr1 with PD166866 Protects Cartilage from the Catabolic Effects Induced by Interleukin-1β: A Genome-Wide Expression Profiles Analysis. (December 2021) - Yi, Lingxian; Lan, Guihua; Ju, Yue; Yin, Xiushan; Zhang, Peipei; Xu, Ye; Weng, Tujun
Objective: Previously we showed that genetic deletion of Fgfr1 in chondrocytes protected mice from progression of osteoarthritis (OA). The aim of this study is to evaluate the effect of PD166866, a potent selective inhibitor of Fgfr1, on cartilage degeneration induced by interleukin-1β (IL-1β) and to clarify underlying global gene expression pattern. Design: Cartilage explants and primary rat chondrocytes were stimulated with IL-1β to establish an inflammatory OA in vitro model. The effects of PD166866 were determined by measuring the release of glycosaminoglycans (GAG) in cartilage explants and primary rat chondrocytes, and the underlying molecular mechanism was analyzed by microarray and RT-PCR analysis in primary chondrocytes. Results: In cartilage explants, PD166866 significantly counteracts IL-β stimulated GAG release. In addition, PD166866 impede IL-1β-stimulated nuclear translocation of p65 in rat chondrocytes. Based on microarray analysis, a total of 67 and 132 genes with more than 1.5-fold changes were identified in IL-1β-treated versus control and PD166866 cotreatment versus IL-1β treatment alone, respectively. Only 19 thereof were coregulated by IL-1β and PD166866 simultaneously. GO and KEGG pathway analysis showed that some pathways, including "cytokine–cytokine receptor interaction, " "chemokine signaling pathway, " and "complement and coagulation cascades, " as well as some key genes like chemokines, complement, and matrix metalloproteinases may relevant for therapeutic application of Fgfr1 blockade in IL-1β-stimulated chondrocytes. Conclusion: Our results clearly demonstrated that blockade of Fgfr1 with PD166866 could effectively suppress the catabolic effects induced by IL-1β, and elucidated whole genomic targets of Fgfr1 inhibition responsible for the therapeutic effects of Fgfr1 blockade against inflammatory OA.